Expansion and Antitumor Cytotoxicity of T-Cells Are Augmented by Substrate-Bound CCL21 and Intercellular Adhesion Molecule 1 - Adutler-Lieber, Shimrit; Friedman, Nir; Geiger, Benjamin (Frontiers in Immunology, 2018)
Adoptive immunotherapy is based on ex vivo expansion and stimulation of T-cells, followed by their transfer into patients. The need for the ex vivo culturing step provides opportunities for modulating the properties of transferred T-cells, enhancing their antitumor abilities, and increasing their number. Here, we present a synthetic immune niche (SIN) that increases the number and antitumor activity of cytotoxic CD8+ T-cells. We first evaluated the effect of various SIN compositions that mimic the physiological microenvironment encountered by T-cells during their activation and expansion in the lymph node. We found that substrates coated with the chemokine CCL21 together with the adhesion molecule intercellular adhesion molecule 1 significantly increase the number of ovalbumin-specific murine CD8+ T-cells activated by antigen-loaded dendritic cells or activation microbeads. Notably, cells cultured on these substrates also displayed augmented cytotoxic activity toward ovalbumin-expressing melanoma cells, both in culture and in vivo. This increase in specific cytotoxic activity was associated with a major increase in the cellular levels of the killing-mediator granzyme B. Our results suggest that this SIN may be used for generating T-cells with augmented cytotoxic function, for use in cancer immunotherapy.